Determination of Knowledge Transfer Implementation on Behavior Adaptation for Solid Waste Disposal: Case Study at Suanluang Sub-District, Amphawa, Samut Songkram - Jeamponk, Paiboon (Ratchaphruek Journal, 2015)
This study aims to investigate the behavioral change in the community towards waste disposal when educated and informed on the matter. Quasi-experimental design was adopted. The research was conducted in communities within Suanluang Sub-district, Amphawa District, Sumut Songkram province, from July to August 2011. The researcher used the specially developed information kit and information on solid waste as instrument in experimenting with experimental and controlled groups of the community. The results showed that the experimental group was more educated on waste disposal ( =13.03) than the controlled group ( =11.83) (sig = .000). While studying the behavior of both the experimental and controlled groups, in terms of solid waste management toward household waste reduction, household waste collection, household waste classification, and household waste disposal was not markedly different.